Differential effects of resource scarcity and pathogen prevalence on heterosexual women's facial masculinity preferences. (16th September 2021) - Saribay, S. Adil; Tureček, Petr; Paluch, Rüzgar; Kleisner, Karel
Abstract: Abstract: The present research focused on how environmental harshness may affect heterosexual women's preferences of potential male mates' facial characteristics, namely masculinity–femininity. The evidence on this issue is mixed and mostly from Western samples. We aimed to provide causal evidence using a sample of Turkish women and Turkish male faces. A video-based manipulation was developed to heighten environmental harshness perceptions. In the main experiment, participants were primed with resource scarcity, pathogen prevalence or neither (control). They then saw masculinised vs. feminised versions of the same faces and indicated the face that they would prefer for a long-term relationship and separately rated the faces on various dimensions. In general, masculinised faces were perceived as slightly more attractive, slightly healthier and much more formidable. A multilevel Bayesian model showed that pathogen prevalence lowered the preference for masculinised faces while resource scarcity weakly elevated it. The overall drop in attractiveness ratings in cases of high perceived pathogen prevalence, one of the strongest effects we observed, suggests that during epidemics, the formation of new relationships is not a favourable strategy. Implications for evolutionary theories of mate preference are discussed.